The Influence of Information and Communication Technology (IEC) on Mothers' Knowledge and Attitudes in Providing Complete Basic Immunization to Infants at the Jikohay Community Health Center, West Obi District - Rahmatia Anwar; Anik Purwati (Pusat Riset dan Inovasi Nasional, 2025)
Complete basic immunization for infants is an important effort in preventing infectious diseases and improving public health. However, certain regions still have subpar vaccination rates, which may be due to parents' ignorance and attitudes. Children who do not receive all recommended vaccinations are more vulnerable to illness and, worse, may die from it. This study was conducted at the Jikohay Community Health Center in the West Obi District to examine the impact IEC on mothers' attitudes and knowledge on the provision of full basic immunizations for newborns. Maternal and child health books (KIA) and a questionnaire approach were used in this qualitative study. The purpose of this study is to ascertain how IEC affects mothers' knowledge and attitudes on giving their babies the recommended basic vaccinations at the Jikohay Health Center in the West Obi District. There were 60 individuals in the population and 40 responders in the sample. Purposive sampling was used for the sample process. The Wilcoxon test was utilized for data analysis. According to the study's findings, 20 respondents had good attitudes, 20 had sufficient attitudes, and 29 had good knowledge, 10 had sufficient knowledge, and 1 had insufficient knowledge after receiving counseling on parental attitudes and knowledge in providing full basic immunizations to infants. At the Jikohay Health Center in the West Obi District, the results of the statistical test with a p-value of 0.000 indicated that IEC had an impact on mothers' attitudes and knowledge toward giving their infants all of the recommended basic vaccinations.